Decoding Polygamy Permits: Unraveling Sociological and Legal Anthropological Perspectives on Marriage Motives and Conditions - Taufiqurohman, Taufiqurohman; Musaffa, M. Ulul Albab (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2023)
Polygamy never runs out to be a subject of study for academics and the general public. One of the derivative issues is the issue of polygamy permits issued by the court. The problem is no longer on whether or not polygamy is allowed, but rather with permission from the court based on the conditions that have been set for those who want to be polygamous. Where these conditions often emphasize the condition of the wife, while the condition of the husband, the polygamous actor has not been given much attention in granting permits. Departing from this background, this paper tries to understand the polygamy permit regulated by stakeholders with a sociological and legal anthropological approach. This approach is used to trace the importance of polygamy permits issued by courts based on the conditions stipulated for polygamy in the realm of sociology and anthropology of Indonesian society itself. As a result, in sociology and legal anthropology, the practice of polygamy in society is based on different motives. Likewise, the granting of polygamy permits the conditions that must be met. The tendency that occurs in the community is that the law is not used as a benchmark in carrying out polygamy. People tend to use their respective customary laws and customs. Thus, the existence of a polygamy permit regulation is one of the preventive efforts to regulate the motives of the marriage by taking into account the conditions that have been agreed upon.